(untitled) (The International Journal for Scientific Research, 2026)
This study evaluates the mineral potential of the Umsalamiyah area in Lawdar District, Abyan Governorate, Yemen, using remote sensing and Geographic Information Systems (GIS) integrated with geochemical analysis and geological field surveys. Landsat 8 and ASTER imagery were analyzed using spectral ratios and indices associated with hydrothermal alterations, clay minerals, and carbonates. Fieldwork included representative rock sampling, followed by X-ray Fluorescence (XRF) analysis. The spectral and geochemical results were integrated within a GIS environment to generate mineral prospectivity maps. Results indicate the superior performance of ASTER imagery in detecting hydrothermal alteration indicators. Geochemical analyses revealed elevated concentrations of strategic elements, particularly iron and niobium, along with magnetite occurrences within pegmatite rocks. The mountainous regions north of the study area showed strong agreement between spectral indicators and structural features, including dense lineaments, suggesting structural control on mineralization. The study confirms that integrating spectral, geochemical, and structural data provides an effective and cost-efficient exploration approach. The Umsalamiyah area is identified as a promising target for future mineral exploration, with recommendations for high-resolution hyperspectral sensing and detailed exploratory drilling.